INSTRUMENT VALIDITY FOR LEARNING RESOURCES ANALYSIS OF DIGITAL DISASTER FOR COASTAL AREAS: AN ANALYSIS OF AIKEN'S V - Eddy Noviana; Intan Kartika Sari; Zufriady; Sri Erlinda; Non Syafriafdi; Putu Eka Suarmika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the instrument validity for digital learning resources for coastal areas based digital in the elementary school by using Aiken's V analysis. The purpose of the research is to develop an instrument that can be seen as the validity for every instrument item to obtain information about the need for digital-based coastal area disaster learning resources in elementary schools. The research approach uses a quantitative approach with a descriptive research method. Instrument design and validation were carried out in three stages; (a) literature review, (b) instrument draft design, and (c) qualitative and quantitative rater review of the instrument. Content validity is validated using the V Aikens coefficient. The content validity coefficient is measured by 8 raters based on the assessment results. It is assessed based on certain scales, which consisted of strongly agree (scale 4), agree (scale 3), disagree (scale 2), and strongly disagree (scale 1). The research results indicate that aspect 1, with four instrument items, is in the high category. For aspect 2, three instruments are in the high category. Aspect 3 with three instruments is in the moderate category. For aspect 4, two instruments are in the moderate category. Aspect 5 with three instruments is in the moderate category. In aspect 5, there are two high-category instrument items and three medium-category instrument items. It is concluded that out of the 22 items of needs analysis, in general, it was valid. Nevertheless, several instrument items needed to be reviewed, namely on the editorial aspect of the statement.